???? ????? ???????? ?? ????? ????????? ??????? ??? ?????? ?????? ??????? ?? ????? ?????? ??? ????????? THE POSITION OF SHEIKH AL-AMRITI IN HIS VIEWS AND GRAMMATICAL TERMINOLOGY BETWEEN BASRA SCHOOL AND KUFA SCHOOL IN DURRAH AL-BAHIYA NUZHUM AL-AJRUMIYAH - Tamim Mulloh (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2020)
Abstract: As for the research problem, what follows is the disclosure of the characteristics of the Basra and Kufa schools, and the position of Sheikh Al-Amriti in his views and grammatical terms between these two schools in Al-Durrah Al-Bahia, the criminal systems. This is Qualitative research because it collects data from words, not numbers. And its data is qualitative data. And the research entry made by the researcher, the descriptive method (Documenter method), which is describing the linguistic aspects without trying to find the causes and causes. That is, it is limited to displaying the linguistic use of a particular group at a specific time and place. It contains an attempt to photograph, record, analyze and interpret the conditions. And the results of the research are the characteristics of the Basra and Kufa schools that are equal between them and violate the criterion for accepting martyrdom and grammatical protest. The position of Sheikh Al-Amriti in his opinions and grammatical terminology in his book